Morpho-Biochemical Modification of Petunia to Saline Water and Salicylic Acid Applications - Khalid M. Elhindi; Fahed A. Almana; Mohammed A. Al-Yafrsi (Horticulturae, 2023)
Petunia (Petunia × hybrida Hort. Vilm.-Andr.) is a well-suited plant for sustainable landscape issues in borderline areas with irrigation with saline water. Salicylic acid (SA) as a modulator performs an imperative function in modulating plant salt tolerance. However, there are a few reports on the effect of SA on petunia plants irrigated with saline water. During the 2022/2023 season, a factorial pot experiment in a randomized complete block design was carried out in Riyadh, Saudi Arabia, to assess the effect of SA concentration (0, 500, 1000, 2000 mgL−1) on petunia plant growth, flowering, ion content, chlorophyll level, and proline concentration under irrigation with salty water (230, 1500, 3000 mgL−1). Saline water up to 3000 mgL−1 dramatically reduced plant growth, chlorophyll, ions, and flowering attributes, while the contrary was observed in proline and sodium concentrations as compared to the control treatments (irrigation with tap water). Foliar spraying with 1000 mgL−1 SA considerably boosted plant growth and flowering as well as chlorophyll, proline, and ion content compared to untreated plants under such salinity levels. Alternatively, the application of 1000 mgL−1 to normal or salinized water significantly decreased the Na content in non-treated plants under such a salinity level. Accordingly, using 1000 mgL−1 of SA under salt stress conditions could be a useful technique to lessen the mutilation induced by the use of salinized water in the era of climate change.